Structural insights into chaperone‐activity enhancement by a K354E mutation in tomato acidic leucine aminopeptidase. Issue 5 (1st May 2016) - DuPrez, Kevin T.; Scranton, Melissa A.; Walling, Linda L.; Fan, Li
Abstract : A K354E mutation in tomato leucine aminopeptidase shifts the oligomerization equilibrium towards lower‐order oligomers, exposing hydrophobic surfaces that are likely to be involved in chaperone activity. Abstract : Tomato plants express acidic leucine aminopeptidase (LAP‐A) in response to various environmental stressors. LAP‐A not only functions as a peptidase for diverse peptide substrates, but also displays chaperone activity. A K354E mutation has been shown to abolish the peptidase activity but to enhance the chaperone activity of LAP‐A. To better understand this moonlighting function of LAP‐A, the crystal structure of the K354E mutant was determined at 2.15 Å resolution. The structure reveals that the K354E mutation destabilizes an active‐site loop and causes significant rearrangement of active‐site residues, leading to loss of the catalytic metal‐ion coordination required for the peptidase activity. Although the mutant was crystallized in the same hexameric form as wild‐type LAP‐A, gel‐filtration chromatography revealed an apparent shift from the hexamer to lower‐order oligomers for the K354E mutant, showing a mixture of monomers to trimers in solution. In addition, surface‐probing assays indicated that the K354E mutant has more accessible hydrophobic areas than wild‐type LAP‐A. Consistently, computational thermodynamic estimations of the interfaces between LAP‐A monomers suggest that increased exposure of hydrophobic surfaces occurs upon hexamer breakdown. These results suggest that the K354E mutation disrupts the active‐site loop, which also contributes to the hexameric assembly, and destabilizes the hexamers, resulting in much greater hydrophobic areas accessible for efficient chaperone activity than in the wild‐type LAP‐A.